FAKTOR- FAKTOR YANG MEMPENGARUHI VIRAL MARKETING ATTITUDE TERHADAP MOBILE VIRAL MARKETING INTENTION - Ridho, Ahmad (AKSIOMA : Jurnal Manajemen, 2022)
Internet users, especially younger ones, spend a lot of time on the Internet to interact with others through various channels and applications such as e-mail, instant messaging, and even online games. The growing use of mobile devices today makes the interaction between individuals online becomes easier and more intense. One of the implications of this condition is the phenomenon of spreading viral content through mobile devices. This provides various impacts for both consumers and marketers. This research attempts to continue several prior research efforts through empirical testing of a mobile viral marketing synthesis model in the Indonesian context. This research uses descriptive research design approach with empirical data collected through an online survey of young generation samples in Jabodetabek. Empirical data is then processed using Structural Equation Modeling approach to test a number of hypotheses proposed. The results of this research conclusion are as follows: 1) Perceived Usefulness proved positively and significantly influence to Viral Marketing attitude, 2) Perceived Ease Of Use not proven positive and not significant to Viral Marketing attitude, 3) Perceived Cost proven negative and not significant to Viral Marketing attitude, 4) Perceived Enjoyment proved to have a positive and significant effect on Viral Marketing attitude, 5) Viral Marketing attitude proved to have a positive and significant effect on Mobile Viral Marketing Intention, 6) Altruism proved to have a positive and significant effect on Mobile Viral Marketing Intention.